2011
DOI: 10.1080/14999013.2011.598601
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Offending During Leave: Development of the Leave Risk Assessment in a Sample of Dutch Forensic Psychiatric Patients

Abstract: The Leave Risk Assessment (LRA) is an actuarial risk assessment tool composed of both historical and treatment-related subscales, developed to assess the risk of serious reoffending by forensic psychiatric patients. This study examines the psychometric properties of the Leave Risk Assessment. The sample was drawn from the same population on which the tool was developed consisting of 195 Dutch forensic psychiatric patients; 78 who re-offended during leave and 117 non-reoffenders. The Leave Risk Assessment had m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Whilst a study of 195 Dutch forensic psychiatric patients reported that 6% of the patients who went on leave during the study period committed an offence while on leave, and at least 64% of these offenses resulted in extremely serious repercussions for the victims, 22 a descriptive analysis of incidents of unauthorised absences from the three English high security hospitals emphasised both the very low rate of absconding from thousands of rehabilitation outings over a five-year period and the minimal risk to the public created by these incidents. 51 These findings were similar to those described in previous studies.…”
Section: Risk Of Harm To the Community From Abscondersmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst a study of 195 Dutch forensic psychiatric patients reported that 6% of the patients who went on leave during the study period committed an offence while on leave, and at least 64% of these offenses resulted in extremely serious repercussions for the victims, 22 a descriptive analysis of incidents of unauthorised absences from the three English high security hospitals emphasised both the very low rate of absconding from thousands of rehabilitation outings over a five-year period and the minimal risk to the public created by these incidents. 51 These findings were similar to those described in previous studies.…”
Section: Risk Of Harm To the Community From Abscondersmentioning
confidence: 99%
“…In the context of making decisions about the management of patients, risk assessment involves collecting information about the patient (including historical factors and dynamic or changeable factors) as well as information about the proposed plan of action and procedural and physical factors before making a prediction of the likelihood of a particular adverse outcome. 22 After first considering possible adverse outcomes in the context of the proposed plan of action, risk management involves scenario (contingency) planning to devise a structure of controls and safeguards which address theoretical or possible risks and reduce the likelihood that a potential adverse outcome will occur.…”
Section: Forensic Orders In Queensland Australiamentioning
confidence: 99%
“…Considering this concern, German forensic-psychiatric hospitals are required to minimize the length of patients' stay by, among others, offering granted leave (13). Such procedure shall encourage patients' rehabilitation and motivate them to participate in further treatment (14,15). In Bavaria, the clinical practice in forensic psychiatry consists of granting leaves to patients, which are temporally limited and gradually escorted, unescorted, inside and offside a high security area (16).…”
Section: Introductionmentioning
confidence: 99%
“…While considerable research attention has been directed towards violence and recidivism prediction after discharge (18)(19)(20)(21)(22), little attention has been paid to the prediction of in-hospital violence (23) or absconding of forensic-psychiatric patients (24,25). Moreover, studies on granted leave decisions have looked primarily on particular aspects such as clinical decision-making, clinicians' subjective perspectives, or novel interactions (14,26,27). With respect to risk assessment Simpson and colleagues (28) found evidence for lower absconding rates after implementation of structured professional judgment (SPJ, 29) within an interdisciplinary team in the decision-making process of granted leave.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation